2017
DOI: 10.5146/tjpath.2017.01386
|View full text |Cite
|
Sign up to set email alerts
|

Intraductal neoplasms of the pancreas: an update

Abstract: ABStRACtwith improvements in imaging to detect silent pancreatic lesions and increases in the number of centers now performing pancreatic surgery, more surgeries have been performed for indications other than invasive carcinoma. This has enormously added to our knowledge of the intraductal neoplasms of the pancreas. In addition, our understanding of the genetics of these lesions has expanded with the introduction of routine molecular genetic analyses. In this review, we provide an update into the most common i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…The EUS findings showed the mass component to be mostly within and along the MPD, suggesting curable ductal neoplasms; therefore, a fine-needle aspiration biopsy was not performed due to the risk of seeding (12). Of course, atypical images of pancreatic ductal adenocarcinoma or IPMN (less the mucinsecreting type) could not be denied; however, intraductal neoplasms, such as intraductal tubular neoplasm, intraductal tubulopapillary neoplasm (13,14), and acinar cell carcinoma (15), were suspected based on the EUS images. Thus far, cases of AIP mimicking malignant IPMN have been reported, showing nodular lesions protruding inside the MPD (7) or branch duct (5,9), as well as wall thickening around the multilocular cyst (8).…”
Section: Discussionmentioning
confidence: 99%
“…The EUS findings showed the mass component to be mostly within and along the MPD, suggesting curable ductal neoplasms; therefore, a fine-needle aspiration biopsy was not performed due to the risk of seeding (12). Of course, atypical images of pancreatic ductal adenocarcinoma or IPMN (less the mucinsecreting type) could not be denied; however, intraductal neoplasms, such as intraductal tubular neoplasm, intraductal tubulopapillary neoplasm (13,14), and acinar cell carcinoma (15), were suspected based on the EUS images. Thus far, cases of AIP mimicking malignant IPMN have been reported, showing nodular lesions protruding inside the MPD (7) or branch duct (5,9), as well as wall thickening around the multilocular cyst (8).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Muraki et al revealed that UCPOGC often show intraductal growth pattern (40%), which may suggest relatively indolent biological behavior of this entity [3], [7]. Differential diagnosis of tumors exhibiting this peculiar growth pattern includes intraductal papillo-tubular neoplasm, and intraductal papillary mucinous neoplasms (MD type), and NET, but small number of cases of acinar cell carcinoma and UCPOGC have been reported as well [1], [3], [4], [5], [15], [16], [17]. Because the lesion in the current report was apparently hypervascular, our preoperative diagnosis of NET was made.…”
Section: Discussionmentioning
confidence: 99%
“…17 Depending on the pancreatic ducts affected, IPMNs can be divided into three groups: (i) main-duct IPMNs (the main pancreatic duct is involved); (ii) branchduct IPMNs (the branches of the main duct are involved); and (iii) mixed IPMNs (the main pancreatic duct and its branches are involved). 3,18,19 This classification is of clinical importance, as it has value in pre-operative algorithms (the main duct IPMNs have a greater risk of revealing high-grade dysplasia or invasive carcinoma). 3,20 However, its significance is over-ridden once the tumour is resected as the presence of invasion and dysplasia grade becomes more important.…”
Section: B I L I a R Y I N T R A -E P I T H E L I A L N E O P L A S I Amentioning
confidence: 99%